A 1.2V improved operational amplifier for bio-medical applications. (25th September 2012) - Santhanalakshmi, M.; Vanathi, P.T.
In this paper, an improved low-power Complementary Metal Oxide Semiconductor (CMOS) programmable operational amplifier for bio-medical applications is presented. The op-amp includes a rail-to-rail input stage, folded cascode stage with class AB biasing and a constant Gm stage. The op-amp is programmed to operate in low-power mode and low noise mode. Simulation results show that the circuit attains a dc open loop gain of 97.75 dB and Common Mode Rejection Ratio (CMRR) of 112.41 dB under a 22 kΩ and 13.5 pF load. The op-amp is realised in 130 nm CMOS technology using Synopsis tool.